Strategi Persaingan dalam Memasarkan Produk Halal di Era Digital - Junida Sari; Juliana Putri (Program Studi Perbankan Syariah, 2026)
This study aims to explain and conclude the competitive strategy in marketing halal products in the rapidly developing digital era and has a very wide reach. This study uses a descriptive qualitative method with a literature study approach, where data is collected from various sources such as books, scientific journals, articles, reports, and other relevant documents related to halal product marketing. The results of the study indicate that the halal product market has experienced significant growth, especially with the support of digital technology that allows fast and wide access to information. This condition triggers increasingly tight competition between business actors, so that appropriate and sustainable strategies are needed. The strategies used include the application of the values of monotheism, Islamic business ethics, and guarantees that the products and services offered truly meet halal standards. Other strategies include the use of digital marketing, training and education of business actors, aggressive promotions, cross-sector collaboration, product innovation, halal tourism development, improving quality and service, and ownership of official halal certificates. The use of social media, e-commerce platforms, and other information technologies are important instruments in building a positive image of halal products and reaching wider consumers, both nationally and globally. This integrated strategy is expected to strengthen the competitiveness of halal products in facing the competitive and ever-changing digital era.